The financial informality in a context of repression of the system: analysis of individual lenders - Urrunaga, Roberto (1988)
The purpose of this article is to explain how the lack of development of the financial system and its performance hold a close relationship with the appearance and growth of the informal capital market, in general, and with the individual informal lenders, in particular. To that effect, the author carries out a theoretical analysis of financial repression and describes its evolution in the Peruvian economy, on the basis of a survey of informal lenders done by GRADE. His study brings him to conclude that the situation of repression has diminished the intermediating role and the attractiveness of the financial system, thus favouring the development of the informal market. He then proposes some steps that must be taken to correct this situation.